Following Clinical Practical Guidelines in Patients with Acute Myocardial Infarction with St Segment Elevation and its Relation with Clinical and Demographic Variables - Francisco de Jesús Valladares Carvajal; Yordano Carlos Ravelo Coma; Lázaro de la Cruz Avilés; Mario Isaac González (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Foundation: acute myocardial infarction with elevation of the ST segment demands a great challenge from health systems. It is vital to rely on clinical practical guidelines. In attaining its degree of adherence may influence clinical and demographic variables. Objetive: to measure the degree of adhesion to Clinical Practical Guidelines in discharged patients with a diagnosis of acute myocardial infarction and ST segment elevation and related to demographic and clinical variables. Method: descriptive study which evaluated the adhesion to clinical practice guidelines in 294 patients by using an instrument of evaluation. The degree of adhesion was related with demographic variables (age and sex) and clinical (selected co-morbidities and state of the patient on discharge). Results: in 76,5 % of the patients the degree of adhesion was adequate. Adequate grading increased accordingly to age (71,3 %, 77,2 % y 82,0 % in patients younger than 60, de 60 a 74 y de 75 and more respectively) and was higher in women (84,1 %). Regarding co-morbidities, the highest percentage of adequate adhesion corresponded to hypertension (77,2 %) and the lowest (69,0 %) to chronic renal disease. Conclusion: a high percentage of ¨graded adequate¨ in adhesion to clinical and practical guidelines was found in patients with acute myocardial infarction and ST segment elevation in the period of study, either in the total of patients so as in any age, sex, co-morbidities selected, discharged alive and deceased groups.